Examining the Reading and Cognitive Profiles of Students With Significant Reading Comprehension Difficulties. (August 2021) - Capin, Philip; Cho, Eunsoo; Miciak, Jeremy; Roberts, Greg; Vaughn, Sharon
This study investigated the word reading and listening comprehension difficulties of fourth-grade students with significant reading comprehension deficits and the cognitive difficulties that underlie these weaknesses. Latent profile analysis was used to classify a sample of fourth-grade students ( n = 446) who scored below the 16th percentile on a measure of reading comprehension into subgroups based on their performance in word reading (WR) and listening comprehension (LC). Three latent profiles emerged: (a) moderate deficits in both WR and LC of similar severity (91%), (b) severe deficit in WR paired with moderate LC deficit (5%), and (c) severe deficit in LC with moderate WR difficulties (4%). Analyses examining the associations between cognitive attributes and group membership indicated students with lower performance on cognitive predictors were more likely to be in a severe subgroup. Implications for educators targeting improved reading performance for upper elementary students with significant reading difficulties were discussed.